Strengthening Corporate Crime Prevention In The Digital Economy In ASEAN - Kristina, Michelle (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2023)
Economic growth and development in the digital era have presented new challenges in structuring business between countries, especially countries in ASEAN. Relations and cooperation between corporations are no longer limited to being within the scope of one country but across countries. Such conditions certainly produce new threats. In addition to the positive impact on corporations by presenting wider markets and development opportunities in ASEAN countries, economic developments in the digital era are also accompanied by negative impacts. This can be seen from the opportunity to commit transnational corporate crimes, such as corruption, and market abuse by conducting covert monopolies and creating an unhealthy economic climate for market growth by presenting unfair competition between capital owners. Such a situation will certainly damage the spirit of solidarity presented by ASEAN when initiating the MEA. Therefore, it is necessary to have an integrated system between countries in ASEAN that covers cooperation between corporations in preventing corporate crime in the era of the digital economy. Furthermore, the government and society can find out every beneficial ownership behind each of corporate crime. This integrated system will help economic actors, communities, and governments to map out the dangers and opportunities that cooperation between corporations in ASEAN countries can provide. A healthy economic climate can be created by presenting a system acceptable to all parties (government, corporate, and society). This research is focus on enhancing measures to prevent corporate crime within the digital economy across ASEAN countries.